Jornalero : being a day laborer in the USA - Ordóñez, Juan Thomas, 1976- (California series in public anthropology., 2015)
"The United States has seen a dramatic rise in the number of informal day labor sites in the last two decades. These sites, typically frequented by immigrant Latin American men---mostly taken to be 'undocumented' immigrants--constitute an important source of unskilled manual labor that sustains building, landscaping, and moving activities in the country. Despite their ubiquitous presence in urban areas, however, much of the research on immigration overlooks day laborers' very existence. While standing in plain view, these men live and work in a precarious environment: As they try to make enough money to send home, they are at the mercy of unscrupulous employers, doing dangerous and underpaid work, and, ultimately, experiencing great threats to their identities and social roles as men. Born and raised in Colombia by an American mother and Colombian father, Juan Thomas Ordóñez spent two years on an informal labor site in the Bay Area, documenting the harsh lives led by some of these men during the worst economic crisis the country has seen in decades. Another Latin American among mainly Mexican and Central American day laborers, he gained a vantage on the immigrant experience based on close relationships with a cohort of men whose lives unravel in a setting of competition, stress, loneliness, and resilience. Both eye-opening and heart-breaking, this account offers a unique perspective on how the informal economy of undocumented labor truly functions in American society"--Provided by publisher.